Short-term outcomes in patients with systemic juvenile idiopathic arthritis treated with either tocilizumab or anakinra. (21st August 2018) - Kearsley-Fleet, Lianne; Beresford, Michael W; Davies, Rebecca; De Cock, Diederik; Baildam, Eileen; Foster, Helen E; Southwood, Taunton R; Thomson, Wendy; Hyrich, Kimme L
Abstract: Objectives: To investigate real-world short-term outcomes among patients with systemic JIA starting tocilizumab or anakinra. Methods: This analysis included all systemic JIA patients within the UK Biologics for Children with Rheumatic Diseases study starting tocilizumab or anakinra between 2010 and 2016. Disease activity was assessed at baseline and one year. At one year the following outcomes were assessed: minimal disease activity, clinically inactive disease, 90% ACR Paediatric response (ACRPedi90). Univariable logistic regression was used to identify baseline characteristics associated with these outcomes. Multiple imputation was used to account for missing data. Results: Seventy-six systemic JIA patients were included (54 tocilizumab; 22 anakinra). More patients starting anakinra as their first biologic compared with tocilizumab (86% vs 63%; P = 0.04), with shorter disease duration (1 vs 2 years; P = 0.003) and higher frequency of prior macrophage activation syndrome (37% vs 8%; P = 0.004). Overall, at one year, 42% achieved ACRPedi90, 51% minimal disease activity, and 39% clinically inactive disease, with similar responses seen between the two drugs. Response was not associated with baseline disease characteristics. Fifteen (20%) patients stopped biologic treatment by one year. Treatment survival was better with tocilizumab (89% at one year vs 59% anakinra; P = 0.002), with three stopping for anakinra injection-related problems. Conclusion: In this real-world cohort of patients with systemic JIA receiving tocilizumab or anakinra, approximately half achieved a minimal disease state by one year. Treatment responses appeared similar between the two therapies albeit with better persistence observed with tocilizumab.